Izvršni in neizvršni direktorji z vidika zastopanja družbe in odškodninske odgovornosti - Rajgelj, Barbara (Pravni letopis, 2009)
Article addresses relationship between executive and non-executive directors in Slovenian one-tier model of corporate governance. The analysis focuses on differences and similarities between both types of directors regarding their competences, in particular their power of representation and liability for damages. As provisions on directors competences are of non-compelling nature, there are many different types of boards of directors in everyday business practice. Their mode of action basically depends on whether the governance structure is divided into executive and non-executive directors and in case of such division whether executive directors are members of the board. If division between executive and non-executive directors doesn't exist, every member of the board represents a company by the law. If the board appoints an executive director from among its members (which is obligatory for listed companies) he/she becomes statutory representative of the company. If the executive directors are appointed from among employees not being members of the board, they are not statutory representatives of the company. In comparison with two-tier board, when the board is divided into executive and non-executive members, the liability of the former is very similar to that of the management board members and liability of the latter is similar to that of the supervisory board members.
Keywords: delniške družbe; gospodarske družbe; management; odškodninska odgovornost; upravljanje; vodenje; vodstveni delavci